Gestational weight gain adequacy and intrapartum oxytocin and cesarean section use: Observational population‐based study in France - Melissa Amyx; Jennifer Zeitlin; Béatrice Blondel; Camille Le Ray (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Research on maternal prepregnancy weight suggests adiposity is associated with dysfunctional labor, but knowledge about how gestational weight gain (GWG) affects labor is sparse. Our objective was to evaluate associations between GWG adequacy and intrapartum obstetric interventions (oxytocin administration; cesarean section) necessitated by labor dysfunction. Material and methods Using national, population‐based French National Perinatal Survey 2016 data, we included term cephalic singleton pregnancies involving trial of labor (n = 9724). For the intrapartum oxytocin administration analysis, we included only women with spontaneous labor (n = 7352). GWG was calculated as the difference between end of pregnancy and prepregnancy weight (both self‐reported) and categorized as insufficient, adequate (reference group), or excessive by prepregnancy body mass index (BMI; underweight <18.5, normal weight 18.5–24.9, overweight 25–29.9, obese ≥30 kg/m2) using the 2009 Institute of Medicine thresholds. Multilevel generalized estimating equation logistic regression models, unadjusted and adjusted for a priori confounders, evaluated intervention‐GWG adequacy associations within BMI categories (under/normal weight combined), stratified by parity (primiparas; multiparas). Results GWG adequacy was associated with oxytocin use among under/normal weight women (primiparas: insufficient 57.3%, adequate 60.8%, excessive 65.0%, p = 0.014; multiparas: insufficient 27.2%, adequate 29.1%, excessive 36.2%, p < 0.001) and overweight primiparas (insufficient 56.0%, adequate 58.7%, excessive 72.5%, p = 0.002). In unadjusted and adjusted models, trends of increased odds of oxytocin administration among women with excessive GWG were found regardless of parity and prepregnancy BMI. Similarly, among under/normal weight women, GWG adequacy was associated with intrapartum cesarean section (primiparas: insufficient 10.7%, adequate 12.7%, excessive 15.3%, p = 0.014; multiparas: insufficient 3.1%, adequate 3.5%, excessive 6.3%, p < 0.001) with increased cesarean section among multiparas with excessive GWG persisting in adjusted models (adjusted odds ratio 1.9, 95% confidence interval 1.3–2.7). However, intrapartum cesarean section was reduced among multiparas with overweight and obese prepregnancy BMI and excessive GWG. Conclusions Excessive GWG was associated with intrapartum oxytocin administration, regardless of parity or prepregnancy BMI, and cesarean section among women with under/normal weight prepregnancy BMI, providing evidence for benefits of healthy GWG for normal labor progression. Additional research is needed to verify our findings and understand differences by BMI.